An investigation on control strategies for fast transient response of SMPS - Jegandren, J.; Gobbi, R.; Athab, Hussain S. (2008)
This paper presents a thorough literature reviews of control methods to improve transient response in switch mode power supply (SMPS). A fast transient response to a step load change is very essential in a power supply. The transient response can be improved by means of feedback control method. There are two feedback control methods widely used for SMPS that are, voltage mode control (VMC) and peak current mode control (PCMC). A simulation study on these feedback control methods has been done using Matlab/Simulink It is found that the PCMC helps the SWS for a faster transient response compared to the VMC. Based on all the reviews a new method is being investigated known as "Voltage Injection Switching Inductor" (VISI) method. This feedback control method provides a better transient response to PCMC. The comparison of these simulation results validates the proposed idea.